The impact of exchange rate policy uncertainty shock on Chinese energy firms' risk-taking - Li, Xiao-Lin; Qiu, Guojing; Ding, Hui (Energy economics, 2022)
This study investigates the causal effect of exchange rate policy uncertainty shock on energy firms' risk-taking, employing the panel data of Chinese listed energy firms during 2003–2019. The results show that a shock of exchange rate policy uncertainty will lead to a significant increase in Chinese energy firms' risk-taking through encouraging these firms to seek for more government subsidies and invest more in financial assets. Moreover, the government subsidy channel is the main channel through which the exchange rate policy uncertainty shock influences the risk-taking of state-owned energy firms, while the financial asset investment channel is the main channel of the shock driving up the risk-taking of non-state-owned energy firms. We also find that the impact of the exchange rate policy uncertainty shock is weaker in energy firms with better growth opportunity and governance structure. These findings suggest that reducing the uncertainty regarding exchange rate policies helps alleviate the adverse shocks to energy firms and is conducive to preventing the potential financial risks. •We explore how exchange rate policy uncertainty shock affects the risk-taking of energy firms in China.•Exchange rate policy uncertainty has a significant positive effect on energy firms' risk-taking.•The effect is less pronounced in energy firms with higher growth opportunity and better corporate structure.•Government subsidy and the development of financialization play a mediating role in the effect.•Reducing the uncertainty regarding exchange rate policies helps lower the risk-taking of energy firms in China.